Land tenancy, soybean, actors and transformations in the pampas: A district balance - Urcola, Hernan Alejandro; De Sartre, Xavier Arnauld; Veiga, Iran; Elverdin, Julio Horacio; Albaladejo, Christophe (2017)
In Argentina, the recent expansion of agriculture has turned into an extreme process almost completely dominated by soybean. The magnitude and speed of soybean expansion are believed to be the main drivers behind social, organizational and economic changes, including the displacement of small-scale producers out of agriculture. Under these transformations, land leasing is a critical management practice and constitutes a link among agricultural actors. This study analyzes changes in land tenancy patterns considering the recent agriculturization process but also older drivers of change. Our results indicate that the expansion of agriculture affects small- and large-scale farms differently, as land renting practices and productive orientation show clear differences by size. In the land leasing market, local producers are the main tenants while sowing pools rent about one quarter of the leased land. The competition for leasing farmland appears to operate within farm sizes. Small- and medium-scale producers compete among them for land, while large-scale local producers compete with sowing pools for the larger plots. Sowing pools do not appear to be the main drivers of land tenancy changes as they are no more relevant than local actors in the land leasing market. However, results suggest that small-scale landowners renting out their land for several years are the ones with higher probabilities of selling their lands. This segment of producers appears to be the one most negatively affected by soybeanization.